2003
DOI: 10.1124/dmd.31.3.282
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Cytochrome P450 Enzymes in Cultured Precision-Cut Human Liver Slices

Abstract: This article is available online at http://dmd.aspetjournals.org ABSTRACT:Precision-cut human liver slices obtained from 11 donors were cultured for 72 h in a defined medium (serum free Williams' medium E) supplemented with 0.1 M insulin and 0.1 M dexamethasone (DEX). Liver slices were treated with 50 M concentrations of ␤ -naphthoflavone (BNF), lansoprazole, rifampicin (RIF), DEX and methylclofenapate and 500 M sodium phenobarbital (NaPB). The relative apoprotein levels of 12 cytochrome P450 (P450) enzymes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 30 publications
(64 reference statements)
3
46
1
1
Order By: Relevance
“…The induction within the brain is striking as CYP2D6 is considered uninducible in the liver by drugs and xenobiotics that readily induce other CYPs (e.g. phenobarbital) (Rae et al, 2001;Edwards et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The induction within the brain is striking as CYP2D6 is considered uninducible in the liver by drugs and xenobiotics that readily induce other CYPs (e.g. phenobarbital) (Rae et al, 2001;Edwards et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The use of these recombinant enzymes provides an effective way to further confirm results obtained for the apparent metabolic pathways using microsomes [29]. However, the rationale for performing the CYP reaction phenotyping for an investigational drug is viable only if CYPs are a major contributor in the overall clearance (>30%) [8,30].…”
Section: Cdna-expressed Recombinant Human Cyp Activitymentioning
confidence: 99%
“…Although microsomes continue to be the first-line screening model for high throughput assays, the number of publications in the last 5 years citing metabolism in hepatocytes has increased by approximately 30% [13], partially due to commercial availability of the cryopreserved cells. Preparation of hepatocytes has been reported in detail by Soars et al [32], while Edwards et al [30] and Lake et al [33] have reported on the preparation of precision-cut human liver slices.…”
Section: Hepatocytes and Liver Slicesmentioning
confidence: 99%
“…toxic, proliferative, degradative) on CYP expression in hepatic tissues we also assessed CYP2D1 as hepatic CYP2D6 is unaltered in smokers and alcohol drinkers and is generally not thought to be an inducible enzyme (Edwards et al, 2003;Mann et al, 2008;Rae et al, 2001;Yue et al, 2008). Linearity and specificity were determined in the same manner as CYP2E1 and CYP2B1/2 (Fig.…”
Section: The Regulation Of Cyp2d1 Following Voluntary Ethanol Intake mentioning
confidence: 99%